The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1128/jvi.00240-11
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Replication of RNA Viruses by ADAR1 via RNA Editing and Inhibition of RNA-Activated Protein Kinase

Abstract: The adenosine deaminases acting on RNA (ADARs) are double-stranded RNA (dsRNA) binding enzymes that catalyze RNA editing of cellular and viral dsRNAs by deamination, which converts adenosines into inosines (6,22,54). Inosine is recognized as a guanosine, and thereby deamination alters the sequence-or structure-specific recognition of RNAs, their translation, and, consequently, the amino acid sequences of several proteins. This process also affects noncoding RNA, and the modification of microRNA (miRNA) sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
90
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 94 publications
(170 reference statements)
1
90
0
Order By: Relevance
“…ADAR1, an A-to-I dsRNA editing enzyme, deaminates adenosine in dsRNA structures, thereby destabilizing dsRNA because I·U base pairs are less stable than A·U pairs (38,47). ADAR1 is known to compete with and suppress PKR activity (38,48). Thus, generation of dsRNA is not restricted to the C KO virus but also appears in parental virus-infected ADAR1 kd cells.…”
Section: Discussionmentioning
confidence: 99%
“…ADAR1, an A-to-I dsRNA editing enzyme, deaminates adenosine in dsRNA structures, thereby destabilizing dsRNA because I·U base pairs are less stable than A·U pairs (38,47). ADAR1 is known to compete with and suppress PKR activity (38,48). Thus, generation of dsRNA is not restricted to the C KO virus but also appears in parental virus-infected ADAR1 kd cells.…”
Section: Discussionmentioning
confidence: 99%
“…The proviral and antiapoptotic activities of ADAR1 have been demonstrated with several viruses, including measles virus, hepatitis delta virus, Venezuelan equine encephalitis virus, yellow fever virus, and HIV (27,31,40,41). ADAR1 deficiency, as illustrated with measles virus, correlates with increased PKR activation (24), increased IFN␤ induction (25), increased SG responses (7), and increased cytotoxicity and apoptosis (25,42).…”
mentioning
confidence: 99%
“…There are two protein size forms of ADAR1 (P110 and P150). ADAR1-P110 is constitutively expressed in ubiquitous types of cells, whereas P150 is only expressed when cells are stimulated by some activators (20,21). The adenosine-to-inosine editing is of broad physiological function.…”
mentioning
confidence: 99%
“…Despite the complexity, ADAR1 has been shown to promote the infection of numerous types of viruses, including VSV; measles virus; EBV; influenza virus; dengue virus; HIV, type 1; human respiratory syncytial virus; and human herpesviruses 8 (20,21). An increasing number of studies have demonstrated that ADAR1-mediated enhancement of viral infections is mainly through RNA editing or inhibition of IFN activity (including both IFN-I production and IFN-activated PKR antiviral activity) (21).…”
mentioning
confidence: 99%